Biofilm based wound care - Wolcott, Randall (Henry Stewart Talks, 2014)
Biofilm in nature, Host biofilm development, Bacterial biofilm & wound healing, Molecular mechanisms of senescence, Planktonic vs. biofilm bacteria, Medical biofilms, Biofilm defences, Antibiotic resistance, Reconstitution of slough, The epithelial gap, Full biofilm debridement, Acute vs. chronic wound, Pyoderma to granulation, Surface management, Sharp debridement, Osteomyelitis, Common skin & skin-structure infection (cSSSI) pathogens, Clinical identification of bacteria, Biofilm-based wound care (BBWC), Multiple concurrent dynamic strategies, Personalized wound care, Negative-pressure wound therapy (NPWT), Cell-based therapy (CBT)